A Study on the Guarantee of the Training Rights for Teachers of Rural Primary School through the Case of the Project of Visiting Famous Schools in the D Primary School of Xi’an in China - Zhi-guo, Zhang (Education Sciences, 2019)
The training for primary school teachers in remote western rural areas of China is relatively weak, thus their training rights cannot be fully guaranteed. Against this backdrop, the project of rural teachers visiting famous schools has been launched since 2005. However, how about the guarantee of rural teachers’ training rights in this project? Through the investigation on the case of the project of visiting famous schools carried out at D primary school in Beilin District, Xi’an City from four aspects: the introduction to the project, the organization and management of trainees and trainers, the recording of the training courses and the interviews with trainees, it is found that the training rights of rural primary school teachers are guaranteed well, but there are still some problems in the training process, such as lack of opportunities for trainees’ demonstration and training administration. More importantly, how to ensure and improve the training quality with the situation of trainers who are lack of background and experience on rural education? This is a problem not only of the development of this project, but of the guarantee of training rights of teachers at rural primary schools.